Inclusion in action : practical strategies to modify your curriculum - Eredics, Nicole (Baltimore : Paul H. Brookes Publishing Co., 2018)
For students working below grade level, curricular modifications can provide equal and meaningful opportunities to learn alongside their same-age peers. This book guides educators on how to modify the curriculum for students with intellectual disabilities participating in the general education classroom, providing 40 strategies that demonstrate how to alter the materials or objectives of a lesson. After introducing the reader to the benefits of inclusive education and to the basics of educating students with intellectual disabilities, the book describes how to design appropriate curricular modifications. Each of the following chapters then presents ten strategies for modifying lessons for Kindergarten through high school in four subject areas: math, English, science, and social studies. Vignettes demonstrate how to implement the strategies for modifying the curriculum in the classroom. A section of printable forms supporting the strategies are included. --
Introduction -- The struggle to include -- What needs to change -- Bridging the gap with this book -- Including all students -- Preparing for inclusion -- Moving from segregation to inclusion -- Core beliefs of inclusive education -- The benefits of inclusive education -- Supporting inclusion schoolwide -- The role of school leadership and staff -- School culture -- School community -- School spaces -- Supporting inclusion in the classroom -- The inclusive classroom team: building a network of support -- Creating an inclusive classroom culture -- Making curriculum accessible through instructional strategies and accommodations -- Ways to make classroom instruction inclusive -- Making curriculum achievable through modifications -- What are curriculum modifications? -- Why modify? -- How are curriculum modifications made? -- Modifying curriculum for students who work below grade level -- Research-based curriculum modifications for inclusion -- Modifications: different ways to make the same curriculum achievable -- Maintaining high standards while modifying curriculum -- Instructional strategies that modify curriculum -- How to use the strategies -- The strategies -- Who benefits from use of these strategies? -- Strategies for knowledge retrieval -- Strategies for comprehension -- Strategies for analysis -- Strategies for knowledge utilization -- Appendix a: helpful resources -- Appendix b: helpful forms -- References -- Index.
Includes bibliographical references : pages 177-181 and index.
Keywords: Curriculum change -- United States; Inclusive education -- Curricula -- United States